The State of Food Security and Nutrition in the World Report: Transforming Food Systems for Affordable Healthy Diets - Torero, Máximo (2020)
Máximo Torero POLICY SEMINAR Virtual Event - Transforming Food Systems for Affordable, Healthy and Sustainable Diets for All: A High-Level Discussion on the Key Findings of the 2020 State of Food Security and Nutrition in the World Report Co-Organized by FAO North America and IFPRI JUL 14, 2020 - 10:00 AM TO 11:30 AM EDT